Subtle Brain Developmental Abnormalities in the Pathogenesis of Juvenile Myoclonic Epilepsy - Gilsoul, Maxime; Grisar, Thierry; Delgado-Escueta, Antonio V.; de Nijs, Laurence; Lakaye, Bernard (Frontiers in Cellular Neuroscience, 2019)
Juvenile myoclonic epilepsy (JME), a lifelong disorder that starts during adolescence, is the most common of genetic generalized epilepsy syndromes. JME is characterized by awakening myoclonic jerks and myoclonic-tonic-clonic (m-t-c) grand mal convulsions and EEG diffuse high amplitude polyspikes. Unfortunately, one third of JME patients have drug refractory disabling awakening m-t-c convulsions and these debilitating seizures recur in 70-80% who attempt to stop antiepileptic drugs (AEDs). To locate networks that drive these m-t-c convulsions in JME, neuropsychological and behavioral studies documented impulsivity, but also impairments in executive functions of organization and feedback, failures that reflect prefrontal lobe disorder. Such prefrontal lobe disorders are also present in siblings of JME patients. To relate such behavioral and neuropsychological abnormalities to brain morphology, quantitative voxel-based morphometry revealed abnormalities of gray matter (GM) volumes in cortical (frontal and parietal) and subcortical structures (thalamus and putamen) and hippocampus. Proton magnetic resonance spectroscopy found decreased NAA/Creatine ratio in thalamic neurons. White matter (WM) integrity was disrupted in corpus callosum and frontal WM tracts. Magnetic resonance imaging (MRI) further unveiled anomalies in both GM and WM structures that were already present at the time of seizure onset. Aberrant growth trajectories of brain development occurred during the first two years of JME diagnosis. Because these neuropsychological, morphological and functional brain MRI imaging results suggest genetic maturational defects in the brain of JME patients and their siblings, disease causing variants were sought, first by positional cloning and most recently, by next generation sequencing. To date, only six genes harboring pathogenic variants (GABRA1, GABRD, EFHC1, Brd2, CasR and ICK) with Mendelian and complex inheritance and covering a limited proportion of the world population, are considered major susceptibility alleles for JME. Evidences on the cellular role, developmental and cell-type expression profiles of these six diverse JME genes, point to their pathogenic variants driving the first steps of brain development when cell division, expansion, axial and tangential migration of progenitor cells (including interneuron cortical progenitors) sculpture subtle alterations in brain networks and microcircuits during development, explaining “microdysgenesis” neuropathology, impulsivity, executive dysfunctions, EEG polyspike waves and awakening m-t-c convulsions of JME.